A BIBLIOMETRIC ANALYSIS OF BOARD DIVERSITY: RESEARCH TRENDS, CHALLENGES, AND FUTURE DIRECTIONS - Christiani, Desi; Widuri, Rindang (Journal of Applied Finance and Accounting, 2024)
Board diversity has become a central issue in corporate governance, with growing recognition of its potential benefits for organizational performance, decision-making, and stakeholder engagement. This paper explores the concept of board diversity, examining various dimensions such as gender, ethnicity, age, and professional background. This study examines the evolution of board diversity, significant trends, and research gaps in current literature through bibliometric analysis. This study employs bibliometric analysis to identify the key areas of research, countries, languages, starting years, top journals, and prolific authors in board diversity. Using (Scopus.Com, n.d.) as the data source, 832 records published between 2016 and 2024 with the keyword "Board Diversity" were analyzed. This research utilized The VOS Viewer software for data analysis. This study implies that the bibliometric analysis highlights essential research gaps and trends, provides a thorough picture of the topic, and points out areas that need more investigation, especially the relationship between corporate success, sustainability, and board diversity. This can direct future studies and give academics and professionals a greater understanding of the strategic value of diverse boards. The results also highlight the regional distribution of research, identifying unexplored areas that can profit from targeted investigations. Ultimately, this study is a valuable tool for anyone wishing to learn more about the changing dynamics of board diversity and how it broadly affects corporate governance.